Adherence to vaccination against SARS-CoV-2 and vaccine safety in patients with immunoglobulin G4-related disease - Linda Mastromanno; Federico Giardina; Angelica Gattamelata; Serena Colafrancesco; Simona Truglia; Francesca Romana Spinelli; Edoardo Simoncelli; Bruno Lucchino; Fabrizio Conti; Roberta Priori (Reumatismo)
Objective. To assess the adherence to the vaccination campaign against SARS-CoV-2 in patients with immunoglobulin-G4-related disease (IgG4-RD) and to evaluate the development of local and systemic adverse events (AEs) following vaccination. Additionally, to investigate the rate and outcome of SARS-CoV-2 infection in IgG4-RD patients.